Romanticism and the rise of history - Bann, Stephen (Twayne's studies in intellectual and cultural history., 1995)
Romanticism and the Rise of History, Bann argues that history came of age in Europe during the period following the French Revolution through the end of the nineteenth century, becoming an object of widespread desire. As one perhaps mildly astonished scholar noted later, it was a time when "the most simple-minded farmhand" was "able to distinguish an old belfry from a new one," and, Bann might add, perceive value in the old one.